The Impact of Electronic Identity Cards and the Digitalization of Certificates on Public Service Effectiveness: A Literature Review - Riskasari, ‎; Ibrahim, Muh Akmal (KnE Social Sciences, 2025)
This study presents a systematic literature review and mapping of 21 selected academic publications from 2015 to 2025, focusing on the digitalization of public services through the implementation of electronic identity cards (e-KTP) and digital certificates. The objective was to explore how digital transformation affects the effectiveness of public administration, particularly in service delivery, transparency, and civil servant (ASN) performance. The findings highlight five key thematic areas: (1) the widespread adoption of digitalization in public services; (2) significant improvements in service efficiency and transparency; (3) multidimensional challenges to implementation, including infrastructural limitations, low digital literacy, and institutional resistance; (4) the essential role of e-governance and community e-readiness in enabling participatory and accountable systems; and (5) the positive, yet conditional, impact on ASN performance. A bibliometric analysis using VOS viewer revealed three dominant research clusters: technology-driven transformation, governance reform and public participation, and civil service capacity building. This study contributes to identifying emerging gaps, particularly in areas such as digital inclusion, ethical governance, and algorithmic oversight, and proposes strategic recommendations for future policy design and research. The results underscore the importance of an integrated, inclusive, and ethically grounded approach to digital public service innovation.